Mewujudkan Sekolah atau Kampus Digital - M. Eka Mahmud (UIN Sultan Aji Muhammad Idris Samarinda, 2011)
The information age is supported by the power of information and communication technology, known as ICT (information communication and technology), has a great influence in the lives of everyday people, such as ways of working and managing organizations (including educational institutions) as well as the perception of the outside world. Thus, interactions between individuals, organizations, communities and countries can be carried out unimpeded by space, time and integrated into the global communications network. Management of the school/university-based digital is managing cultural change, values, and ways to communicate and interact in the education building. Strategic steps undertaken to get to school / university digital is the establishment of an agency that works to provide accelerated programs school/university digital works; work easier for the technical operational issues related to the digital world, he worked his support to all operational difficulties be easy.